The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1163/15691330-12341439
|View full text |Cite
|
Sign up to set email alerts
|

Rituals, Emotional Entrainment and National Identification

Abstract: Although the effects of nationalized mega-events on national identification have been theorized and examined by a number of studies, little is known about the specific mechanisms that bring about changes in people’s attitudes towards their country. The authors hypothesize that during nationwide rituals, in particular sports mega-events, participants experience collective emotional entrainment in the context of national symbols and practices that in turn increases their identification with their nation. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…There are always pre-contractarian grounds of contracts: feelings, values, beliefs. Yet while I am inclined to grant Mellor and Schilling some level of universal embodiment (and partly the point of this book is to point out that even among those for whom liberalism is most deeply embedded and whose interests it most serves we nonetheless see a lack of resonance, which might suggest that there is always something continuous beneath the discursive surface), it is important not to neglect the wealth of theory regarding discourse as performative, and repetitive performance as entraining a way of understanding and feeling into the body (Collins 2004;Winchester 2008;Scheve et al 2017;Dougherty 2018). From this perspective, it must be the case that sex -and friendship, and faith, and exchanging goods and services -does different things depending on how it is framed.…”
Section: The Social As Contractmentioning
confidence: 99%
“…There are always pre-contractarian grounds of contracts: feelings, values, beliefs. Yet while I am inclined to grant Mellor and Schilling some level of universal embodiment (and partly the point of this book is to point out that even among those for whom liberalism is most deeply embedded and whose interests it most serves we nonetheless see a lack of resonance, which might suggest that there is always something continuous beneath the discursive surface), it is important not to neglect the wealth of theory regarding discourse as performative, and repetitive performance as entraining a way of understanding and feeling into the body (Collins 2004;Winchester 2008;Scheve et al 2017;Dougherty 2018). From this perspective, it must be the case that sex -and friendship, and faith, and exchanging goods and services -does different things depending on how it is framed.…”
Section: The Social As Contractmentioning
confidence: 99%
“…16) that emerges from the synchronization of attention and behaviour in the group. Since then, researchers have applied the concept of collective effervescence to social protests (e.g., Castro-Abril et al, 2021), sporting events (e.g., von Scheve et al, 2017), live artistic performances (e.g., Liebst, 2019) and everyday social interactions (Collins, 2014), such as watching movies together (e.g., Gabriel et al, 2020). A meta-analysis of studies on collective effervescence supported Durkheim's hypothesis: individuals reported feeling connected, identified to other individuals and committed to their group when they experienced emotional arousal during social events (Pizarro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%